Transformation of Traditional Values to the Phenomenon of Santri Courtship in the Digital Era - Zaini, Abdul Wahid; Hamidah, Tutik (JURNAL ISLAM NUSANTARA, 2023)
This research aims to analyze how traditional values in Islamic boarding schools have transformed in the context of the dating phenomenon among Islamic boarding school students in the digital era. Using a qualitative phenomenological approach, this research explores the influence of communication technology, such as social media, on student dating, which was previously strictly controlled by Islamic boarding school norms. Data was collected through observations, in-depth interviews, and document analysis, providing an in-depth picture of interactions between students and the use of digital media in romantic contexts. The research results show that Islamic boarding school students use social media as a means of dating, which often deviates from hard-line traditional values. This research identifies new dynamics where traditional and modern values collide and interact, creating a third space where norms and values are shaped and renegotiated. The implications of this research are essential for Islamic boarding school caregivers in formulating educational strategies relevant to today's technology and for policymakers in designing interventions that balance traditional values and students' freedom in the digital era.